ANALISA PEMANFAATAN KOMPOS SEBAGAI MEDIA BIOCOVER DI TEMPAT PEMROSESAN AKHIR SAMPAH: Studi Kasus Kota Depok, Jawa Barat - Gabriel Andari Kristanto; Dwi Rahayu; Evy Novita (Dept. of Chemical Engineering, Diponegoro University, 2014)
High percentage of organic waste in urban areas makes composting as good alternative in waste processing. However, composting has not been effectively used and the result is not optimal. Previous studies found compost can be used as biocover media to reduce methane emission landfill. The objective of the study is to identify the characteristic of produced at temporary waste unit Depok, West Java and the effect of compaction toward the amount of methane removal in the landfill. Before applied as biocover media, compost was characterized followed by maturation process. Study on methane removal efficiency was conducted as batches in four reactors for 35 days with compaction rate varying from 750, 800, 850 dan 900 kg/m3. Composting media used in the research had 80 cm thickness with artificial gas consisting of 50% CH4 dan 50% CO2. Initially, compost did not meet criteria as mature compost based on SNI 19-7030-2004, and as media biocover hence a pre-treatment was needed to improve the quality compost to meet the requirements. Compaction rate of 900 kg/m3has highest elimination capacity of methane i.e. 98,31%±3,6% and 13,98±4,32 g/m3/hour.